Bimbingan Teknis Perkoperasian Kepada Anggota PRIMKOPPOLRES Madiun Jawa Timur T.A. 2023 - Prayitno; Eny Kusumawardhani; Alysia Eva Yuni Setyawati; Mohamad Nur Efendi (Universitas Merdeka Madiun, 2024)
This Community Service was held at Primkoppolres Madiun. Primkoppolres Madiun Cooperative is established and managed for the benefit of police members who are a group of police officers in a certain jurisdiction, such as in districts or cities. The technical guidance was held with the hope of increasing the knowledge and potential of members, which will automatically impact the improvement of business results from Primkoppolres. The methods used in implementing the activities include providing handouts for reading materials related to the training topics Practical Book along with a CD on cooperatives. Conducting socialization/lectures given by competent speakers in the fields of taxation and cooperatives, as well as discussions. From the questionnaire results distributed to participants, it is stated: basically, participants understand the material provided and find it beneficial to broaden their knowledge in the field of cooperatives and taxation, which is one of the fields of accounting. Participants also hope that similar activities can be carried out in the coming years.